2018
DOI: 10.2147/ott.s174498
|View full text |Cite|
|
Sign up to set email alerts
|

Natural borneol is a novel chemosensitizer that enhances temozolomide-induced anticancer efficiency against human glioma by triggering mitochondrial dysfunction and reactive oxide species-mediated oxidative damage

Abstract: BackgroundTemozolomide (TMZ)-based chemotherapy represents an effective way for treating human glioma. However, its clinical application is limited because of its side effects and resistance to standard chemotherapy. Hence, the search for novel chemosensitizers to augment their anticancer efficiency has attracted much attention. Natural borneol (NB) has been identified as a potential chemosensitizer in treating human cancers. However, the synergistic effect and mechanism of NB and TMZ in human glioma have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Cisplatin is one of the most common chemodrugs that can inhibit cancer cell proliferation by inducing caspase-mediated apoptosis (Zhang et al 2014). Previous studies showed the potential of NB in enhancing chemodrug-induced apoptosis Liu et al 2018;Meng et al 2018). Here, we provide convincing evidence that NB potentiated the anticancer efficacy of cisplatin through the induction of caspase-9-mediated cell apoptosis.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Cisplatin is one of the most common chemodrugs that can inhibit cancer cell proliferation by inducing caspase-mediated apoptosis (Zhang et al 2014). Previous studies showed the potential of NB in enhancing chemodrug-induced apoptosis Liu et al 2018;Meng et al 2018). Here, we provide convincing evidence that NB potentiated the anticancer efficacy of cisplatin through the induction of caspase-9-mediated cell apoptosis.…”
Section: Discussionsupporting
confidence: 62%
“…ROS is a critical upstream initiator in cellular signalling cascades, which modulate various cellular events, including cell growth, metastasis, and apoptosis (Apel and Hirt 2004;Pelicano et al 2004). Previous studies have shown that the accumulation of intracellular ROS is closely related to NB-mediated chemo-sensitization (Zhang et al 2014;Liu et al 2018). Herein, our data demonstrated that the combined treatment of cisplatin with NB remarkably increased the intracellular accumulation of ROS in comparison with single treatment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Acted synergistically with curcumin-based drugs [251,252]. Acted synergistically with temozolomide [253].…”
Section: Increased Doxorubicin-induced Interference Withmentioning
confidence: 99%
“…However, clinically, the desired effect of postoperative radiotherapy or chemotherapy are often difficult to achieve mainly due to the frequent development of tolerance to radiation or chemotherapy in tumor cells.Previous research has shown that borneol can open the blood-brain tumor barrier by regulating the expression of TJPs protein[25]. In addition, studies have revealed the role of borneol as a new type of chemotherapy sensitizer inducing mitochondrial dysfunction and oxidative damage, which promotes the anticancer effect of temozolomide on human glioma cells[26]. However, it is still unclear whether borneol could exert an apoptosis effect on malignant gliomas.…”
mentioning
confidence: 99%